Servicios al cliente de la Despensa Prieto de la ciudad de Babahoyo - Morán Cabezas, Meyster Analy (2021)
The purpose of this case study is to analyze in a technical way the Customer Service of the Pantry "Prieto" in the city of Babahoyo, in order to determine the main problems that the organization has that harm users choosing to emigrate to the competition that is more aggressive and innovative every day. The following information is supported by those directly involved in the investigation, such as the owner manager and consumers, through essential data collection tools such as the interview and survey carried out respectively with the aforementioned actors. This research was developed based on the conditions of the deductive method, which helped to determine the particular causes that have caused Customer Service to be increasingly deteriorated in the entity, together with a descriptive-bibliographic methodology, the Failures found were correctly detailed, validating key information provided by the various means of verifying knowledge as a pillar to support what is described in the current document.